Nitriding of steel 40x with a high-intensity ion beam - Ryabchikov A. I. Aleksandr Ilyich; Chan My Kim An; Koval T. V. Tamara Vasilievna; Sivin D. O. Denis Olegovich; Ananin P. S. Petr Semenovich; Korneva O. S. Olga Sergeevna (2018, 2018)
Title screen